## 4everjames 3 years ago Solve the following system of equations by using the substitution method. x - y = 3 2x + 2y = 2

1. waterineyes

Multiply the first equation by 2 both the sides, tell me what you got?

2. 4everjames

@waterineyes 4x+4y=2

3. waterineyes

I said multiply 2 to the first equation.. What is your first equation?

4. 4everjames

@waterineyes 2x-2y=3

5. waterineyes

Why are you not multiplying 2 with right hand side.. I said to multiply both the sides. Now tell me what you get..

6. 4everjames

@waterineyes 2x-2y=6

7. waterineyes

Yes.. Now add the two equations: 2x - 2y = 6 2x + 2y = 4 Add them..

8. 4everjames

@waterineyes 4x+4y=10

9. waterineyes

What will be the result when you do this: -2y + 2y = ???

10. 4everjames

@waterineyes 0. so y

11. 4everjames

i dont understand what you just did

13. 4everjames

@4everjames friend i wrote the answer step by step in 5 minutes.

15. 4everjames

x=2 and y=-1

17. 4everjames

@muhammad9t5 thats what i got. thanks

18. 4everjames

@muhammad9t5 Solve the following system of equations by using the elimination method. 2x - 3y = -10 3x + 5y = 4

20. 4everjames

@4everjames friend do you need ans of 2nd question or explanation?

22. 4everjames

friend now it will take time and i am gonna sleep now i wll give expanation tomorrow. please

24. 4everjames